PROS1 novel splice site variant decreases protein S expression in patients from two families with thrombotic disease - Menezes, Juliane (2017)
Protein S (PS) is a widely studied protein with an important function in the downregulation of thrombin formation. Since its discovery in 1976, more than 400 variants have been described in PS gene (PROS1) associated with PS deficiency and as a risk factor for venous thromboembolism (VTE). We describe a novel variant, c.1871-14T>G, in intron 14 of PROS1 gene identified in two patients with PS deficiency from two unrelated families with a history of thrombotic disease. This alteration leads to a PROS1 mRNA expression reduction, probably due to nonsense-mediated mRNA decay. Our results suggest that c.1871-14T>G is causative of type I PS deficiency in these patients, highlighting the importance of screening not only the coding and the most conserved intron–exon junctions, but also perform mRNA-based studies. We call attention to the potential increased risk of VTE in hereditary type I PS deficiency associated with this cryptic splice-site variant.